Satisfaction with human resource management practices and turnover intention in a five-star hotel : the mediating role of perceived organizational support - Duarte, Ana Patrícia (2015)
Employees’ satisfaction with human resources management (HRM) practices has been envisaged as a solid predictor of turnover; nonetheless, how these practices may influence employee’s behavior is still an unclear process. There are suggestions that HRM practices may be distal determinants of turnover, as their effects may be mediated by more proximal variables such as perceived organizational support. This study empirically tested a model of research arising from these theoretical suggestions in a five-star hotel. The data collected from the survey of 152 workers were subjected to structural equation analyses. The results showed that the theoretical model had a strong fit to the data, giving empirical support to the prediction that satisfaction with HRM practices reduces turnover intentions, by increasing perceived organizational support. The importance of these results is discussed and interpreted from the point of view of strategic gains associated to the quality of HRM practices for the management of voluntary turnover.